Endogenous Uteroglobin as Intrinsic Anti-inflammatory Signal Modulates Monocyte and Macrophage Subsets Distribution Upon Sepsis Induced Lung Injury - Janicova, Andrea; Becker, Nils; Xu, Baolin; Wutzler, Sebastian; Vollrath, Jan Tilmann; Hildebrand, Frank; Ehnert, Sabrina; Marzi, Ingo; Störmann, Philipp; Relja, Borna (Frontiers in Immunology, 2019)
Sepsis is a serious clinical condition which can cause life-threatening organ dysfunction, and has limited therapeutic options. The paradigm of limiting excessive inflammation and promoting anti-inflammatory responses is a simplified concept. Yet, the absence of intrinsic anti-inflammatory signaling at the early stage of an infection can lead to an exaggerated activation of immune cells, including monocytes and macrophages. There is emerging evidence that endogenous molecules control those mechanisms. Here we aimed to identify and describe the dynamic changes in monocyte and macrophage subsets and lung damage in CL57BL/6N mice undergoing blunt chest trauma with subsequent cecal ligation and puncture. We showed that early an increase in systemic and activated Ly6C+CD11b+CD45+Ly6G− monocytes was paralleled by their increased emigration into lungs. The ratio of pro-inflammatory Ly6ChighCD11b+CD45+Ly6G− to patrolling Ly6ClowCD11b+CD45+Ly6G− monocytes significantly increased in blood, lungs and bronchoalveolar lavage fluid (BALF) suggesting an early transition to inflammatory phenotypes during early sepsis development. Similar to monocytes, the level of pro-inflammatory Ly6ChighCD45+F4/80+ macrophages increased in lungs and BALF, while tissue repairing Ly6ClowCD45+F4/80+ macrophages declined in BALF. Levels of inflammatory mediators TNF-α and MCP-1 in blood and RAGE in lungs and BALF were elevated, and besides their boosting of inflammation via the recruitment of cells, they may promote monocyte and macrophage polarization, respectively, toward the pro-inflammatory phenotype. Neutralization of uteroglobin increased pro-inflammatory cytokine levels, activation of inflammatory phenotypes and their recruitment to lungs; concurrent with increased pulmonary damage in septic mice. In in vitro experiments, the influence of uteroglobin on monocyte functions including migratory behavior, TGF-β1 expression, cytotoxicity and viability were proven. These results highlight an important role of endogenous uteroglobin as intrinsic anti-inflammatory signal upon sepsis-induced early lung injury, which modules the early monocyte/macrophages driven inflammation. Short Summary Blunt chest injury is the third largest cause of death following major trauma, and ongoing excessive pro-inflammatory immune response entails high risk for the development of secondary complications, such as sepsis, with limited therapeutic options. In murine double hit trauma consisting of thoracic trauma and subsequent cecal ligation and puncture, we investigated the cytokine profile, pulmonary epithelial integrity and phenotypic shift of patrolling Ly6ClowCD11b+CD45+Ly6G− monocytes and Ly6ClowCD45+F4/80+ macrophages to pro-inflammatory Ly6ChighCD11b+CD45+Ly6G− monocytes and Ly6ChighCD45+F4/80+ cells in blood, lungs and bronchoalveolar lavage fluid (BALF). Pro-inflammatory mediators and phenotypes were elevated and uteroglobin neutralization led to further increase. Enhanced total protein levels in BALF suggests leakage of respiratory epithelium. In vitro, uteroglobin inhibited the migratory capacity of monocytes and the TGF-β1 expression without affecting the viability. These results highlight an important role of endogenous uteroglobin as an intrinsic anti-inflammatory signal upon sepsis-induced early lung injury, which modulates the early monocyte/macrophages driven inflammation.